Method for determining the maximum density and optimal moisture content of coarse soils (Texas Journal of Engineering and Technology, 2022)
This article presents the results of a study to determine the maximum density and optimal moisture content of coarse soils with clay and sand aggregates using large-size SoyuzDorNII device. Values of maximum density and optimum moisture content were recommended depending on the size of the fraction.